PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI SEKRETARIAT DIREKTORAT JENDERAL PENGELOLAAN PEMBIAYAAN DAN RISIKO KEMENTERIAN KEUANGAN - Oktaviani, Evi; Darmo, Ika Suhartanti (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
This research aimed to determine whether there is influence between Training and Work Motivation to Employee Performance of Directorate General of Financing and Risk Management Ministry of Finance of Indonesia. This research uses the quantitative method. The number of samples in this research was 50 respondents. This research uses the purposive sampling method to determine the samples with the criteria of employees who had attended training in 2016 – 2017. Method of completion of data used in this research were a questionnaire, interviews, and research literature. The result of t-test shows a significant influence of training variable on employee performance with t-value 2.382, meanwhile work motivation variable does not significantly affect the employee performance with t-value 1.654. Training and Work motivation variables simultaneously have an effect of 21.3% on employee performance. Keywords: training, motivation, performance